The Bio-Synthesis of Three Metal Oxide Nanoparticles (ZnO, MnO2, and MgO) and Their Antibacterial Activity Against the Bacterial Leaf Blight Pathogen - Ogunyemi, Solabomi Olaitan; Zhang, Muchen; Abdallah, Yasmine; Ahmed, Temoor; Qiu, Wen; Ali, Md. Arshad; Yan, Chengqi; Yang, Yong; Chen, Jianping; Li, Bin (Frontiers in Microbiology, 2020)
Xanthomonas oryzae pv. oryzae (Xoo) is the most infectious pathogen of rice, which causes bacterial leaf blight (BLB) disease. However, the accumulation of chemical or antibiotic resistance of Xoo necessitate the development of its alternative control. In this study, we biologically synthesize three metal oxide nanoparticles (ZnO, MnO2, and MgO) using rhizophytic bacteria Paenibacillus polymyxa strain Sx3 as reducing agent. The biosynthesis of nanoparticles was confirmed and characterized by using UV-vis spectroscopy, XRD, FTIR, EDS, SEM, and TEM analysis. The UV Vis reflectance of the nanoparticle had peaks at 385, 230, and 230 nm with an average crystallite particle size 62.8, 18.8, and 10.9 nm for ZnO, MnO2 and MgO, respectively. Biogenic ZnO, MnO2, and MgO nanoparticles showed substantial significant inhibition effects against Xoo strain GZ 0006 at a concentration of 16.0 µg/ml, for which the antagonized area was 17, 13 and 13 mm and the biofilm formation was decreased by 74.5, 74.4, and 80.2%, respectively. Moreover, the underlining mechanism of nanoparticles was inferred to be in relation to the reactive oxygen species based on their antibacterial efficiency and the deformity in the cell wall phenomenon. Overall, an attractive and eco-friendly biogenic ZnO, MnO2, and MgO nanoparticles were successfully produced. Altogether, the results suggest that the nanoparticles had an excellent antibacterial efficacy against BLB disease in rice plants, together with the increase in growth parameter and rice biomass. In conclusion, the synthesized nanoparticles could serve as an alternative safe measure in combatting the antibiotic-resistant of Xoo.